L’ethnopoétique et l’anthropologie structurale à partir d’un récit de Victoria Howard, Chinook Clakamas - Catharine Mason (Journal de la Société des Américanistes)
Ethnopoetics and structural anthropology as seen through a narrative by Victoria Howard, Clackamas Chinook. The study of a Clackamas Chinookan myth told by Victoria Howard to the linguist, Melville Jacobs, in 1930 provides the basis for a comparison of two methodologies of myth analysis. The approach of structural anthropology, innovated by Claude Lévi-Strauss and applied in his interpretation of Howard’s text with relation to other narrations of this samemyth, is placed side by side with an ethnopoetic analysiswhich is based on the internal logic of an individual narrative. This article seeks to demonstrate the compatibility of these two scientific approaches using concrete elements of the text. It also points to common objectives of these two approaches, both practical and theoretical, in the study of oral tradition.